Peculiarities Of Aspects Of Information Exchange In The Information Society - Dono Kalandarova (International Journal of Advanced Science and Technology, 2020)
This article is dedicated to the ideas, stages and development of an informed society. A number of scientific views and theoretical foundations of the contents, types, types, basic functions and features of the exchange of information, which is one of the main parts of the information society, are analyzed and argued. And also, the scientific views and conclusions of Western and Russian researchers in the field of information security are presented. The article puts forward the ideas of the influence of information on public consciousness and the formation of personal identity.